Penerapan Tata Kelola Keuangan Berbasis Akuntansi Terkomputerisasi Sebagai Upaya Peningkatan Usaha Kopi Sendang Tulungagung - Meme Rukmini; Wiwiek Andajani; Afif Yudha Tripariyanto; Otaviana Wahyu Prihardini; Mayciella So (Jurnal Ilmiah Pangabdhi, 2022)
The problems faced by Omah Kopi Mandiri and UMKM Karya Perdana "Kopi Pendekar" start from not having an expense notebook, income notebook and main notebook. The marketing carried out is only limited to collectors and certain areas. In addition, the coffee fryer used still uses human labor and the resulting capacity is low. With these various problems, the service team provided solutions in the form of training on the preparation of financial reports in accordance with SAK EMKM and Socialization on Special Taxation of MSMEs. So that marketing can be reached widely, you can use social media and marketplaces. Procurement of coffee fryers with a large capacity so that it can help both partners in fulfilling orders from consumers.